Natural Antisense Transcripts in Plants: A Review and Identification in Soybean Infected with Phakopsora pachyrhizi SuperSAGE Library - Suzana de Aragão Britto-Kido; José Ribamar Costa Ferreira Neto; Valesca Pandolfi; Francismar Corrêa Marcelino-Guimarães; Alexandre Lima Nepomuceno; Ricardo Vilela Abdelnoor; Ana Maria Benko-Iseppon; Ederson Akio Kido (The Scientific World Journal)
Natural antisense ranscripts (NAT) are RNA molecules complementary to other endogenous RNAs. They are capable of regulating the expression of target genes at different levels (transcription, mRNA stability, translation, etc.). Such a property makes them ideal for interventions in organisms' metabolism. The present study reviewed plant NAT aspects, including features, availability and genesis, conservation and distribution, coding capacity, NAT pair expression, and functions. Besides, an in silico identification of NATs pairs was presented, using deepSuperSAGE libraries of soybean infected or not with Phakopsora pachyrhizi. Results showed that around 1/3 of the 77,903 predicted trans-NATs (by PlantsNATsDB database) detected had unitags mapped in both sequences of each pair. The same 1/3 of the 436 foreseen cis-NATs showed unitags anchored in both sequences of the related pairs. For those unitags mapped in NAT pairs, a modulation expression was assigned as upregulated, downregulated, or constitutive, based on the statistical analysis (P<0.05). As a result, the infected treatment promoted the expression of 2,313 trans-NATs pairs comprising unitags exclusively from that library (1,326 pairs had unitags only found in the mock library). To understand the regulation of these NAT pairs could be a key aspect in the ASR plant response.